Investigation of standard test condition requirement in establishing alternative measurement platform for photovoltaic cell - Nik Fatin Qistina, Amran; Wan Nur Ainna Amirah, Wan Zulkifli; Norazila, Jaalam; Faiz, Arith; Ahmad Syahiman, Mohd Shah (IOP Publishing, 2024)
The output characteristics of any solar modules or solar cells are typically assessed according to the standard requirements known as Standard Test Conditions (STC). To meet the STC requirement before commercializing products, manufacturers must subject every fabricated solar cell or module to various tests. These tests include conducting current-voltage characteristics under specific conditions: a solar irradiance of 1000 W/m², a cell temperature of 25°C, and an air mass (AM) of 1.5. This study investigates this STC requirements for developing an alternative measurement platform for photovoltaic cells, specifically focusing on current-voltage characterization of solar cells. Utilizing calibrated photovoltaic cells, the optimal angles for Air Mass 1.0 and 1.5 was identified to be 48.2° and 41.8° respectively. Main methodology was segregated in three stages: first, correlating solar irradiance and illuminance under different light conditions, both outdoor and indoor; second, designing a system with a cooling device to stabilize cell temperature at 25°C; and third, developing a platform to meet AM 1.0 and 1.5 requirements. Results demonstrated varying irradiance outputs for sunlight, halogen lamps, and LED Grow Lights, with the latter achieving 810.2 W/m² under AM 1.5. The study also established optimal voltage and current settings for temperature stabilization, achieving 25°C in 3 minutes. Although the proposed solar simulator design did not reach the targeted 1000 W/m², it offers a feasible low-cost alternative for small-scale applications. The research underscores the technical viability of developing cost-effective solar simulators that meet STC requirements, despite challenges in achieving high irradiance levels with LEDs.